Kerja Anatomi Tubuh dalam Yoga - Ni Made Adnyani (Jurnal Yoga dan Kesehatan, 2018)
Anatomy is a field of knowledge that studies the structure of the human body. A good understanding of anatomyand its relationship to asanas is essential so that yoga practitioners can keep their body safe, comfortable andthe mind remains stable. Yoga has an integrated working principle in the human body. An important element thatdistinguishes yoga practice with other exercises is the linkage of breath, posture and movement. By the yogis, theyare based on the concept of prana and apana; sthira and sukha; brahmana and laghana; and sukha and dukha. Theflow of breath is associated with prana and apana, postural stability associated with sthira and sukha, and sukha duhka and movements associated with brahmana and laghana.